Evidence of cerebral hypoperfusion consecutive to ultrasound‐mediated blood‐brain barrier opening in rats. Issue 6 (23rd January 2023) - Labriji, Wafae; Clauzel, Julien; Mestas, Jean‐Louis; Lafond, Maxime; Lafon, Cyril; Salabert, Anne‐Sophie; Hirschler, Lydiane; Warnking, Jan M.; Barbier, Emmanuel L.; Loubinoux, Isabelle; Desmoulin, Franck
Abstract : Purpose: This work aims to explore the effect of Blood Brain Barrier (BBB) opening using ultrasound combined with microbubbles injection on cerebral blood flow in rats. Methods: Two groups of n = 5 rats were included in this study. The first group was used to investigate the impact of BBB opening on the Arterial Spin Labeling (ASL) signal, in particular on the arterial transit time (ATT). The second group was used to analyze the spatiotemporal evolution of the change in cerebral blood flow (CBF) over time following BBB opening and validate these results using DSC‐MRI. Results: Using pCASL, a decrease in CBF of up to 29 . 6 ± 15 . 1 % $$ 29.6± 15.1% $$ was observed in the target hemisphere, associated with an increase in arterial transit time. The latter was estimated to be 533 ± 121ms $$ 533± 121ms $$ in the BBB opening impacted regions against 409 ± 93ms $$ 409± 93ms $$ in the contralateral hemisphere. The spatio‐temporal analysis of CBF maps indicated a nonlocal hypoperfusion. DSC‐MRI measurements were consistent with the obtained results. Conclusion: This study provided strong evidence that BBB opening using microbubble intravenous injection induces a transient hypoperfusion. A spatiotemporal analysis of the hypoperfusion changes allows to establish some points of similarity with the cortical spreading depression phenomenon.